Association between Board characteristics and earnings quality: Malaysian Evidence - Redhwan Ahmed AL-Dhamari,; Ku Nor Izah Ku Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2014)
The present study examines the relationship between board characteristics and earnings quality after the amendment of the Malaysian Code on Corporate Governance in 2007. Using heteroskedasticity-corrected least square regressions upon a sample of Malaysian firms listed in 2008 and 2009, the study finds that the quality of earnings is higher among firms with independent chairmen than among those firms with non-independent chairmen. However, in contradiction to the expectations of the study, inconclusive results are found concerning board independence. The results also demonstrate that investors do not perceive board size as a good indicator of quality earnings. The findings imply that investors continue to have reservations regarding the ability of boards to enhance the quality of earnings, although efforts have been made to reform corporate governance following the Asian financial crisis. The study serves as a signal to policy makers to evaluate the importance of board mechanisms when enhancing financial reporting quality in emerging markets.